Pengaruh Perbandingan Jeruk Manis (Citrus sinensis L.) Dengan Pepaya (Carica papaya L.) Terhadap Karakteristik Marmalade - Widyagana Jaya, I Komang Sedana; Timur Ina, Putu; Diah Puspawati, Gusti Ayu Kadek (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p09, 2023)
This research aimed to determine the effect of comparison sweet orange and papaya on characteristics of marmalade and the comparison between sweet orange and papaya that is able to produce marmalade with the best characteristics. The experimental design used was Randomized Blok Design with the treatment factor of the sweet orange with papaya that is: 100%:0; 90%:10; 80%:20%; 70%:30%; 60%:40%; 50%:50%. The treatment was repeated 3 times to obtain 18 units of experiment. The data obtained were analyzed by ANOVA and if the treatment had significant effect on the observed variables then continued with the Duncan Multiple Range Test. The result showed comparison between sweet orange with papaya haf significant effect on vitamin C, total soluble solids, viscosity, color L*a*b*, hedonic test (color, aroma, texture, taste, and overall acceptance), and scoring test (color and taste) marmalade. Comparison of 50% sweet orange : 50% papaya was the best characteristics of marmalade with vitamin C 95.23 mg/100g, total soluble solids 63.17%brix, viscosity 30,000.00 cP, color by L* value 21.00, a* value 42.13, and b* value 43.00, color reddish orange and liked, taste typical of orange and liked, aroma, texture, and overall acceptance was liked.